Perancangan Game Edukasi 2D Tentang Keselamatan di Rumah untuk Anak Usia Dini - Slamet Widodo; Meiyi Darlies; Sania, Widia (Jurnal Teknologi Informatika Multimedia Digital, 2024)
Manners should be known to children as early as possible. Age 6-8 years is the right age to introduce children to manners. The importance of providing an introduction to manners from an early age to foster a sense of empathy in children. To introduce good manners to children cannot be done in a monotonous way, active children need entertainment in learning and understanding the material. Board games are here as a medium that supports the introduction of manners in an interesting and fun way. This study has the following objectives: (1) Designing a Manner Castle board game visualization using Digital Illustration Techniques with Whimsical style as a medium for introducing manners to children aged 6-8 years, (2) Educating children aged 6-8 years about daily manners day in an interesting and fun way through the Manner Castle board game. The development method used in this board game media is Design Thinking which includes the steps: Data Collection (Empathize), Needs Analysis (Define), Conceptualization (Ideate), Making ( Prototype), and Test (Test). The results of this study are in the form of a board game media entitled Manner Castle about the introduction of adab. This board game media has been validated by media experts and material experts and tested on children aged 6-8 years